(untitled) (Research, Society and Development, 2022)
Introduction: Tuberculosis is the leading cause of death from infectious diseases, followed by tuberculosis-HIV co-infection. Knowing the social determinants that support the incidence of co-infection can enable the implementation and adaptation of public policies aimed at prevention, early diagnosis and adherence to treatment for both infections. Objective: To identify, from the main sociodemographic aspects of tuberculosis-HIV co-infection in Brazil addressed in the literature, the Social Determinants of Health (DSS) that are linked to the development of this co-infection. Methodology: This is a descriptive and qualitative study carried out through an integrative literature review, which included the search and analysis of materials indexed in the LILACS, PubMed and SciELO databases, published in Portuguese, English and Spanish, among the years 2011 and 2021. Results and discussion: After analyzing the materials, 10 works were selected for the composition of this study. The sociodemographic profile found was: male, between 20 and 39 years old, with up to 11 years of schooling. Among the risk factors are alcoholism, drug use and dependence, and AIDS. The DSS found were: gender patterns, unfavorable socioeconomic conditions, social exclusion and others. Conclusion: Through the survey carried out, it was possible to identify many variables and social determinants of health associated with the development of co-infection, mainly demonstrating unfavorable economic and behavioral situations. Therefore, it is necessary to develop joint strategies for public policies, paying attention to the most relevant determinants.